Analysis Of Potential Drug Interactions In Prescribing Type 2 Diabetes Mellitus Patients At A Pharmacy In Medan City - Kiki Rawitri Kiki; Sri Wahyuni; Syilvi Rinda Sari (International Journal of Health and Pharmaceutical (IJHP), 2022)
Multiple drugs or polypharmacy received by patients with diabetes mellitus (DM) during therapy can trigger drugrelated problems, one of which is drug interactions. The occurrence of drug interactions causes uncontrolled blood sugar levels which can affect the patient's morbidity, mortality, and quality of life. This study aims to look at the description of potential drug interactions in prescribing type 2 DM patients at a Pharmacy in Medan City for the period January-April 2022. This study is a descriptive study and data were taken retrospectively on 126 prescription sheets for type 2 DM patients who met the inclusion criteria. Identification of potential drug interactions using online literature such as Medscape Drug Interaction Checker, Drugs.com, and Drug Interaction Fact 2009 e-book. Data analysis was carried out univariately to describe the percentage of drug interactions. The results showed that from 126 prescription sheets for type 2 DM patients there were 108 patients (85.71%) who had the incidence potential drug interactions with a total of 238 potential drug interactions. The number of potential drug interactions based on the mechanism of action, namely pharmacodynamic interactions were 117 events (49.15%), pharmacokinetic interactions were 22 events (9.24%), and unknown were 99 events (41.61%) with The severity level was severe (major) with 1 event (0.42%), moderate (moderate) with 223 events (93.69%) and mild (minor) with 14 events (5.89%). Based on the results of the study, it was concluded that an analysis of 126 patients with type 2 diabetes mellitus, there were found 108 (85.71%) prescriptions to potential antidiabetic interactions.